A systematic review and meta-analysis of antimicrobial resistance in paediatric acute otitis media. (August 2019) - Mather, Michael W.; Drinnan, Michael; Perry, John D.; Powell, Steven; Wilson, Janet A.; Powell, Jason
Abstract: Objective of review: Acute otitis media (AOM) is the largest cause of antimicrobial prescriptions amongst children in developed countries. Excessive and inappropriate prescribing is known to drive antimicrobial resistance, but less is known of antimicrobial resistance in AOM-associated bacteria. Type of review & search strategy: We conducted a systematic review and meta-analysis of bacterial prevalence and antimicrobial resistance in studies of paediatric AOM identified from Ovid Medline, Embase and the Cochrane library. Results: From 48 unique studies, 15, 871 samples were included. Only 0.67 (CI 0.63–0.71) of all ear samples grew a bacterial pathogen. The most common bacterial causes of AOM in children were Streptococcus pneumoniae 0.30 (CI 0.27–0.32), Haemophilus influenza 0.23 (CI 0.20–0.26), and Moraxella catarrhalis 0.05 (CI 0.04–0.06). Resistance patterns varied amongst organisms and antimicrobial agents. The pooled proportion of bacterial culture-positive episodes of AOM that could be effectively treated with amoxicillin was 0.85 (CI 0.76–0.94), erythromycin was 0.64 (0.48–0.78) and amoxicillin-clavulanate was 0.95 (CI 0.85–0.98). Conclusion: We have demonstrated the bacteriology and antimicrobial resistance patterns of AOM. Of samples which grew bacteria, on average approximately 15% of isolates demonstrated resistance to amoxicillin; a typical first-line agent. Greater understanding of local bacteriology and resistance patterns is needed to enable improved antimicrobial stewardship. Highlights: Two in three samples from middle ear sampling in AOM grew a bacterial pathogen. Common bacterial causes of AOM include Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. Antimicrobial resistance to first-line antibiotics is common. Amoxicillin-clavulanate offers a higher chance of bacterial eradication than current first-line agents. A greater understanding of local bacteriology and resistance patterns is needed to enable improved antimicrobial stewardship.